Local Properties of Measures in Quantum Field Theory and Cosmology - Velhinho, J.M. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We show that measure theoretical results concerning the Ashtekar-Lewandowski measure in the space of generalized connections have direct analogues in the context of the Bohr compactification of the line and associated Haar measure. We present also a characterization of the support of the measure associated with the canonical quantization of the free massive scalar field, following closely well known analogous results concerning the Euclidean path integral measure.